Use of medicinal plants in traditional health care practices: A case study in Talwandi Sabo, Bathinda District, Punjab (India) - Kaur, Kuljinder; Kaur, Amandeep; Thakur, Sweta (Current Botany, 2020)
A comprehensive study was conducted to document the available medicinal plants and their traditional applications among the local people from July 2018 to June 2019 in Talwandi Sabo town of Bathinda District of Punjab. Purposive sampling method was used to select traditional medicinal practitioners of the study area. A semi-structured questionnaire was prepared and personal interviews were conducted to gather firsthand information about ethno-medicinal plants. Analysis of data revealed the use of 88 medicinal plant species belonging to 77 genera and 42 families for the treatment of about 60 ailments. The highest number of plants were used for gastrointestinal problems, skin problems followed by respiratory diseases, skeletomuscular diseases and dental problems. Traditional healers are still playing a great role in the primary health care system of Talwandi Sabo. Some practitioners were ensuring the 100% results of their formulations against many serious diseases. Further, the scientific validation of these formulations should be done for getting new alternative medicines against these diseases.